Abdominal complications due to collapse of a large mesenteric hematoma after rupture of a right colic artery aneurysm: a case report - Taro Ikeda; Masaaki Mitsutsuji; Takuya Okada; Isamu Yamada; Ryunosuke Konaka; Yukari Adachi; Akiko Matsumoto; Takahiro Wada; Naoki Harada; Masahiro Samizo (Surgical Case Reports)
Abstract Background Non-traumatic mesenteric hematomas are usually well controlled, with no resulting symptoms. Herein, we report a case in which collapse of a large mesenteric hematoma, after rupture of a right colic artery aneurysm, caused small bowel obstruction and rapid absorption of the hematoma contributed to cholestasis. Case presentation A-44-year-old man presented with a sudden onset of severe right lower abdominal pain. Computed tomography (CT) revealed rupture of a right colic artery aneurysm and intra-abdominal bleeding. After embolization of the right colic artery aneurysm, a large mesenteric hematoma remained. As the patient had no symptoms, we elected to pursue conservative treatment. However, on day 16 post-onset, he developed right lower abdominal pain. On CT imaging, partial collapse of the wall of the residual mesenteric hematoma was observed, with visible leakage from the hematoma into the abdominal cavity, resulting in small bowel obstruction and cholestasis. Symptoms did not improve with conservative treatment, and we proceeded to surgical treatment on day 32 after onset. Intra-operatively, adhesions between the small bowel and the abdominal wall were identified and caused the small bowel obstruction. We proceeded with removing these adhesions and as much of the hematoma as possible. Although the small bowel obstruction improved after surgery, cholecystitis developed, and percutaneous transhepatic gallbladder aspiration was performed on day 45. The patient was discharged on day 70. Conclusions Collapse of a mesenteric hematoma can cause small bowel obstruction. Rapid absorption of the hematoma due to the collapse might contribute to cholestasis. A large abdominal hematoma might be a risk factor for failure of conservative treatment, and surgery might be required due to abdominal complications.